SSR analysis of the Medicago truncatula SARDI core collection reveals substantial diversity and unusual genotype dispersal throughout the Mediterranean basin - Ellwood, Simon; D'Souza, N.; Kamphuis, L.; Burgess, T.; Nair, R.; Oliver, Richard (2006)
The world’s oldest and largest Medicago truncatula collection is housed at the South Australian Research and Development Institute (SARDI). We used six simple sequence repeat (SSR) loci to analyse the genetic diversity and relationships between randomly selected individuals from 192 accessions in the core collection. M. truncatula is composed of three subspecies (ssp.): ssp. truncatula, ssp. longeaculeata, and ssp. tricycla. Analysis at the level of six SSR loci supports the concept of ssp. tricycla, all the samples of which showed unique alleles at two loci. Contingency Chi-squared tests were significant between ssp. tricycla and ssp. truncatula at four loci, suggesting a barrier to gene flow between these subspecies. In accessions defined as ssp. longeaculeata, no unique allelic distribution or diagnostic sizes were observed, suggesting this apparent ssp. is a morphological variant of ssp. truncatula. The data also suggest M. truncatula that exhibits unusually wide genotype dispersal throughout its native Mediterranean region, possibly due to animal and trade-related movements. Our results showed the collection to be highly diverse, exhibiting an average of 25 SSR alleles per locus, with over 90% of individuals showing discrete genotypes. The rich diversity of the SARDI collection provides an invaluable resource for studying natural allelic variation of M. truncatula. To efficiently exploit the variation in the SARDI collection, we have defined a subset of accessions (n=61) that maximises the diversity.